2018
DOI: 10.1007/s13187-018-1420-y
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to Educating Smokers About Lung Cancer Screening: a Qualitative Study of Decision Making Experiences in Primary Care

Abstract: We sought to qualitatively explore how those at highest risk for lung cancer, current smokers, experienced, understood, and made decisions about participation in lung cancer screening (LCS) after being offered in the target setting for implementation, routine primary care visits. Thirty-seven current smokers were identified within 4 weeks of being offered LCS at seven sites participating in the Veterans Health Administration Clinical Demonstration Project and interviewed via telephone using semi-structured qua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(27 citation statements)
references
References 59 publications
1
22
0
Order By: Relevance
“…Many more benefits than harms could be given by current smokers in a qualitative study with telephone interviews. This is due to several factors, such as fear of LC; shame, self-blame and futility-not able to quit so better to detect it early; perceived ability of LCS to quantify and measure risks and harms; deference to providers, lack of interest and understanding of numerical risk information, which are all leading to 'see it more positive than it is' (37).…”
Section: Recruitment: Extra Barriers Specific For (Ex-)smokers?mentioning
confidence: 99%
See 1 more Smart Citation
“…Many more benefits than harms could be given by current smokers in a qualitative study with telephone interviews. This is due to several factors, such as fear of LC; shame, self-blame and futility-not able to quit so better to detect it early; perceived ability of LCS to quantify and measure risks and harms; deference to providers, lack of interest and understanding of numerical risk information, which are all leading to 'see it more positive than it is' (37).…”
Section: Recruitment: Extra Barriers Specific For (Ex-)smokers?mentioning
confidence: 99%
“…This leads to patients just following the recommendations of their PCP (without having had a 'shared decision') (17). Smokers made decisions not based on a mental calculus of the trade-offs, but instead on selective understanding of risks and benefits distorted by feelings aroused by the offer of screening and the recommendations and interpersonal relationships with their primary care physician (37).…”
Section: Recruitment: Extra Barriers Specific For (Ex-)smokers?mentioning
confidence: 99%
“…Research has demonstrated that black men are more responsive to health messages that are specifically targeted to them ( Woods et al, 2004 ). The inclusion of culturally relevant information has been reported to be effective in improving health outcomes but has rarely been included in decision aids ( Alden et al, 2014 ; Covvey et al, 2018 ; Greene et al, 2018 ; Hoffman et al, 2015 ; Hung et al, 2019 ; Mohkles et al, 2018 ). These findings indicate that addressing cultural beliefs and barriers is imperative to the successful design, implementation, and effectiveness of decision aids for lung cancer screening.…”
mentioning
confidence: 99%
“…The facilitation of SDM has been posited to be dependent upon a trusting and empowering relationship between patient and provider (Greene et al, 2019; Truglio-Londrigan, & Slyer, 2018), but the way in which patients and providers interact to make health care decisions, and the importance of the patient-provider relationship in decision-making have not been fully explored or adequately measured (Elwyn et al, 2003; Kriston et al, 2010; Melbourne et al, 2010).…”
mentioning
confidence: 99%
“…Most research exploring experiences with health care decision-making has involved patients (Edwards & Elwyn, 2006; Edwards et al, 2001; Entwistle et al, 2004; Greene et al, 2019; Moreau et al, 2012; Su et al, 2020; Verberne et al, 2019), but there is little research considering the provider experience (Elwyn et al, 2001; Ford et al, 2003; Friedberg et al, 2013), and these studies do not directly address the importance of the relationship between patient and provider in making health care decisions. The patient-provider relationship is an important element in any clinical interaction, and one that is proposed to be an indicator of effective decision-making, particularly in the context of patient-centered care delivery (Elwyn et al, 2001; Marteau et al, 2001; Melbourne et al, 2010; Simon et al, 2007; Truglio-Londrigan & Slyer, 2018).…”
mentioning
confidence: 99%